Brain distribution and release of Cholecystokinin octapeptide - Hudson, Anne Mary (Division of Chemical Pathology, 2018)
In this thesis the in vitro release of immunoreactive CCK₈ (iCCK₈) from rat central nervous system preparations and the regulation of this release have been studied. Rat brain was dissected into the following regions; hypothalamus, cerebral cortex, striatum and thalamus, according to the method of Brownstein, Arimura, Sato et. al. (1975). CCK₈ was found to be distributed throughout these regions (range of 9 - 300 pmoles), with the highest concentration in cortex (300 pmol). In addition, low levels (range 9 - 30 pmoles) of CCK₈ were found in spinal cord, brain stem and cerebellum, in agreement with other workers. Immunohistochemical techniques have demonstrated CCK-like immunoreactivity in nerve cell bodies and fibres throughout brain, particularly in the cortex. Subcellular fractionation of rat brain was used to study the subcellular localisation of CCK. Tissue was homogenised to shear off nerve terminals (synaptosomes) which were purified and used to study the release of the peptide from hypothalamic and extrahypothalamic nerve endings.